Student Representation of Indigent Defendants and the Sixth Amendment: On a Collision Course - Hardaway, Robert M. (1980)
This article will review the parallel patterns of development of clinical education and the sixth amendment, highlighting areas in which the practices of the former either conflict, or contain the potential for conflict with the latter. An analysis will be made of the present legal status of law student representation of indigent criminal defendants, with reference primarily to constitutional and sixth amendment considerations, but also to such related matters as the confidentiality of student-client communications, law student professional responsibility, and the applicability to students of state bar disciplinary rules. Finally, guidelines will be proposed regarding the proper scope of student practice and methods by which student representation of indigent defendants can be brought into compliance with the sixth amendment